2018
DOI: 10.1371/journal.pone.0204109
|View full text |Cite
|
Sign up to set email alerts
|

Refining muscle geometry and wrapping in the TLEM 2 model for improved hip contact force prediction

Abstract: Musculoskeletal models represent a powerful tool to gain knowledge on the internal forces acting at the joint level in a non-invasive way. However, these models can present some errors associated with the level of detail in their geometrical representation. For this reason, a thorough validation is necessary to prove the reliability of their predictions. This study documents the development of a generic musculoskeletal model and proposes a working logic and simulation techniques for identifying specific model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…Full datasets for 1 representative high-functioning patient and 1 lower-functioning patient demonstrating this variability are available at https://doi.org/10.5518/319. Previous studies have demonstrated that applications of musculoskeletal models can be used to reliably predict contact forces for a large cohort of patients during gait [26,27]. It was previously shown that different patient characteristics influence both kinematics [28] and loads experienced at hip [27], with patient's overall functionality being a highly influential factor in determining variability in kinematics and kinetics during gait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Full datasets for 1 representative high-functioning patient and 1 lower-functioning patient demonstrating this variability are available at https://doi.org/10.5518/319. Previous studies have demonstrated that applications of musculoskeletal models can be used to reliably predict contact forces for a large cohort of patients during gait [26,27]. It was previously shown that different patient characteristics influence both kinematics [28] and loads experienced at hip [27], with patient's overall functionality being a highly influential factor in determining variability in kinematics and kinetics during gait.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal simulations were performed using a commercially available software (AnyBody Modeling System, version 7.1, Aalborg, Denmark). A detailed musculoskeletal model of the lower limb [26] based on a cadaveric dataset [31] was scaled to match the anthropometrics of each patient based on marker data collected during a static trial [32]. Marker trajectories and GRF data from each gait trial served as input to an inverse dynamics analysis, based on a third-order-polynomial muscle recruitment criterion, to calculate muscle forces and HCFs.…”
Section: Musculoskeletal Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We modified the model by calibrating the each muscle's passive muscle force-length curves so that joint moments generated by passive muscle forces more closely matched experimental data 55 . We also altered the muscle paths of the hip abductor musculature to more closely match moment arms estimated from experiments 56,57 , finite element models 58 , and MRI 59 (See Supplemental Material). The modified model was scaled to match the anthropometric measurements taken from the static trial, and virtual markers on the model were moved to match experimental marker locations during this trial.…”
Section: Simulation-based Intervention Designmentioning
confidence: 99%
“…The effort to create valid muscle-driven MS models spans dozens of years in the context of noninvasive analysis of gait, posture, and reaching movements (Arnold et al, 2010;Carbone et al, 2015;De Pieri et al, 2018;Delp et al, 1990;Gritsenko et al, 2016;Horsman, 2007;Rajagopal et al, 2016;Saul et al, 2015b). The models are typically developed using minimalistic sets of parameters and with additional testing of model performance against experimental observations (Kirchner, 2006).…”
Section: Introductionmentioning
confidence: 99%